Pengaruh Kemandirian Belajar Siswa Terhadap Hasil Belajar Matematika Materi Pecahan Siswa Kelas III SD Negeri 5 Rambutan - Desi Rahmawati; Misdalina Misdalina; David Budi Irawan (Journal on Education, 2023)
Independent learning is an active way of learning for students, students who have a high will when learning, and students who have the initiative to learn on their own without being told by others. This study aims to determine the effect of student learning independence on the results of learning mathematics in fraction material. This research used in this study is a correlational study using the product moment formula. The sample used was students of class III.B SD Negeri 5 Rambutan. In this study, before using the hypothesis test, a prerequisite test was carried out first, namely the normality test and it was declared to be normally distributed. Then do a correlation test and get the results rxy = 0.830. Test the hypothesis using the t-test. The results of testing the hypothesis obtained significant values in questionnaires and tests, namely 5,953 where ttable = 2.120 with df = n-2 where n = 18 so df = 16 with level α = 0.05, so it can be concluded tcount = 5,953 ≥ ttable = 2.210 then Ha is accepted and Ho is rejected, or there is an influence of student learning independence on the mathematics learning outcomes of fractional material for third grade students at SD Negeri 5 Rambutan.